Pathways to Industrialization and Regional Development - Scott, Allen J.; Storper, Michael (Taylor & Francis, 1992)
The world has seen a shift in socio-economic relations, in the patterns and processes of industrialization and regional development. The social regulation of the economic order, flexible production organization and industrial district formation have brought periods, places and pathways to the heart of economic debate. Pathways to Industrialization and Regional Development provides a platform from which to address a new economic order. All the major schools of thought are represented. Focussing upon the interactions between economic logic and political institutions at both the local and global levels, the authors set the agenda for the 1990s.